PENGEMBANGAN KARAKTER KEPEMIMPINAN SISWA MELALUI KEGIATAN EKSTRAKURIKULER PASKIBRA DI SMA NEGERI 2 BANJARBARU - Adini Nur Karimah, Rizkia; Kiptiah, Mariatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of student leadership character is one of the important goals of education that is not only oriented towards academic aspects, but also the formation of student character. The Paskibra extracurricular activity is one of the means that plays a role in developing leadership character through the habit of responsibility and self-confidence. However, the results of pre-observation at SMA Negeri 2 Banjarbaru indicate that the development of student leadership character through Paskibra activities has not been running optimally in all members. This study aims to describe the development of student leadership character through Paskibra extracurricular activities at SMA Negeri 2 Banjarbaru. The study used a qualitative method with data collection techniques through interviews, observation, and documentation. Research informants consisted of the principal, teachers, supervisors, trainers, and students. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, while data validity was tested through triangulation, member checking, use of reference materials, and extended observation. The results of the study indicate that Paskibra extracurricular activities play an important role in developing student leadership character through the formation of responsibility and self-confidence. Character development is carried out through instilling discipline, adherence to rules, carrying out tasks, actively participating in training, and providing opportunities for students to lead and perform in public. The program's success is supported by the role of the principal, teachers, mentors, coaches, and adequate facilities and infrastructure. Despite facing various obstacles, such as low motivation, excessive gadget use, laziness, fatigue, and low self-confidence among some students, the Flag Raising Team (Paskibra) continues to make a significant contribution to shaping students' leadership character.